Factors that Impact on Quality of Life of People with Disease with Tremor: Systematic Review - Gomes, Ricardo Zanetti; Gomes, Luisa Pereira de Oliveira Zanetti; Celinski, Vitória Rossetim; Martins, Camila Marinelli; El Sayed, Omar; Fillos, Letícia; Chaicoski, Andrielle Cristina (International Journal of Innovative Research in Medical Science, 2022)
Background: Parkinson’s disease and essential tremor are common diseases that cannot be cured. These diseases cause a major impact on the patients’ lifestyle, and as they are progressive over time, their symptoms tend to get worse as well as these individuals’ quality of life. Objective: To analyze how the duration of the disease impact quality of life and other aspects related to the disease. Methods: A systematic review was carried out, and a meta-analysis developed including original articles published after 2006 that assessed the quality of life of patients with diseases that presented tremor as a symptom. Results: The number of papers found totaled 7.114, out of those, 27 were included in the systematic review, and 15 of them were also included in the meta-analysis. The articles found analyzed sociodemographic, neuropsychiatric scales, and disease severity scales. In the meta-analysis we found that the time of disease impacts the score of PDQ-39 in numbers of dominants, the mini-mental score, and the UPDRS score. Conclusion: Longer time of disease since diagnostic results in a negative impact on the patients’ quality of life, cognition, emotional status, activities of daily living, motor examination, and therapy complication.